Peran Brand Ambassador, Brand Awareness, Customer Trust, Electronic Word of Mouth Terhadap Minat Beli Sepatu - Fahriyan Wahyu Nugroho; Tri Septin Muji Rahayu; Wida Purwidianti; Arini Hidayah (ARBITRASE: Journal of Economics and Accounting, 2025)
This study aims to examine the influence of Brand Ambassador, Brand Awareness, Customer Trust, and Electronic Word of Mouth (e-WOM) on the interest in buying Vans shoes among students in Purwokerto. The study used a quantitative approach with the type of associative research, the sampling technique with purposive sampling obtained 125 respondents from three universities. Data analysis was carried out using the Partial Least Squares (PLS) method. The results of the study showed that the four variables, namely Brand Ambassador, Brand Awareness, Customer Trust, and e-WOM, had a positive and significant effect on buying interest. These findings prove that the selection of the right Brand Ambassador, increased brand awareness, maintained consumer trust, and  effective management of e-WOM can increase interest in buying Vans shoes among students. The results of this study are expected to be an input for brand marketing strategies in the younger generation segment.